Cofiring characteristics of coal blended with torrefied Miscanthus biochar optimized with three Taguchi indexes. (1st April 2019) - Huang, Chao-Wei; Li, Yueh-Heng; Xiao, Kai-Lin; Lasek, Janusz
Abstract: The main purpose of this study was the optimization of torrefaction conditions for biochar cofiring with new Taguchi indicators. However, the combustion characteristics of biochar cofiring in different furnaces and reactors are distinct. Examining optimal torrefaction conditions using the Taguchi method based on maximum energy or mass yields is paradoxical. Accordingly, three indicators, that is S index, proximate-based index (PA index), and elemental-based index (EB index), were proposed for solid fuel combustion. To study the combustion behavior of biochar torrefied under optimal conditions, a single pellet combustor was employed to record the characteristic time and gas emission at various reaction regions. Furthermore, the effects of ambient temperature and biomass blending ratio (BBR) on combustion behavior were investigated in the single pellet combustion experiment. When the temperature was increased to 600 °C, the ignition delay time ranged from 8 to 29 s, whereas at 800 °C, the fuels were ignited within 4 s of each other. The total combustion times were shortened as the reaction rate increased. The total combustion time of Australian coal, raw Miscanthus, 50% blended biochar (S index), 50% blended biochar (PB index), and 50% blended biochar (EB index) were shortened by 19.3%, 18.9%, 14.2%, 12.9%, and 13.5%, respectively. Highlights: The optimization of torrefaction conditions for biochar cofiring is employed. Three indicators for the Taguchi method were proposed for solid fuel combustion. The effects of ambient temperature and BBR on combustion behavior were investigated. The ignition delay and char combustion times for biochar were linearly proportional to the BBR. PB index is derived on proximate analysis, while EB index is derived on elemental analysis.